Analysis Of Groundwater Conservation Policy In Provincial Regulation Of South Kalimantan Number 5 Of 2018 On Groundwater Management Reviewed From Ecological Fiqh - Hidayatullah Hidayat; Nasrullah Nasrullah; Suci Utami; Firzana Utari (Syariah: Jurnal Hukum dan Pemikiran, 2022)
For maintaining the existence and preservation of natural resources, in this case namely the Provincial Government of South Kalimantan has organized a groundwater conservation program. However, this policy must in accordance with the provisions of Islamic teachings because this district is inhabited by the majority of the Muslim community. The research aims to describe the overview of groundwater conservation policy in the Provincial Regulation of South Kalimantan Number 5 of 2018 on Groundwater Management and an ecological fiqh perspective on the groundwater conservation policy. This study uses the literature study method with a normative juridical approach. Its’ legal material is the Provincial Regulation of South Kalimantan Number 5 of 2018 on Groundwater Management and other related regulations. The results showed that the groundwater conservation policy in South Kalimantan was carried out with three programs, namely: groundwater protection and preservation, groundwater conservation and groundwater conservation, and determination of groundwater conservation zones. The policy is implemented by involving community participation. The groundwater conservation policy of South Kalimantan Province in terms of Ecological Jurisprudence is a form of embodiment of the teachings of environmental wisdom that can strengthen intellectual and spiritual aspects, including the concept of monotheism.